Synthesis and Appraisal of Natural Drug-Polymer-Based Matrices Relevant to the Application of Drug-Eluting Coronary Stent Coatings - Bakhtawar Ghafoor; Murtaza Najabat Ali; Zainab Riaz (Cardiology Research and Practice)
Cardiovascular diseases are becoming a leading cause of death in the world, and attention is being paid to develop natural drug-based treatment to cure heart diseases. Curcumin, ginger, and magnolol are pharmaceutically active in many ways, having properties including anticoagulation, antiproliferation, anti-inflammatory, and antioxidant, and may be used to synthesis coatings for drug-eluting stents to treat cardiovascular diseases. In the present investigation, a degradable polymer with varying molecular weights was used as a drug carrier to control the degradation of polymer; three different natural drugs such as curcumin, magnolol, and ginger were used owing to their reported pharmacological properties. The results of in vitro measurements of all three natural drugs released from drug-loaded polymeric films showed an initial burst release followed by a sustained release for up to 38 days of measurement. On the other hand, different levels of hemocompatibility were observed by varying concentrations of natural drugs in human erythrocytes. As per the ASTM F756 standard, ginger having low concentration showed optimum hemocompatibility with regard to the drug-eluting stent application as compared with magnolol and curcumin concentrations, which showed suboptimal hemocompatibility and fall in the range of mild-to-severe blood toxicity category. The structure of the coating films was characterized by Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) with results suggesting that there was no chemical bonding between the polymer and drug. Thus, according to this study, it can be concluded that after more detailed in vitro testing such as hemocompatibility tests and platelet adhesion testing, ginger can be a better candidate as a drug-coating material for drug-eluting stent applications.